Parenting Patterns of Children and Family Functions in Social Capital Perspective - Muh Hanif (International Journal of Social Science and Religion (IJSSR), 2023)
Parenting is a form of interaction influencing each other between parents and children. This way of relating is reflected in the attitude and behavior of parents towards their children. Children experience continuous growth according to their age. Internal and external factors, such as parenting style, interaction patterns in the family, family roles and responsibilities, home and school support, and several other supporting aspects, influence a child's ability to complete developmental tasks. Parents apply various parenting styles to children, such as authoritarian, democratic, and permissive. Democratic parenting tends to provide the greatest benefits for the healthy development of children. Social factors such as social bonds, norms, values, and social trust in parenting also support child development, and family function in maximizing children's developmental tasks and preventing violence against children